A review of state estimation of humanoid robot targeting the center of mass, base kinematics, and external wrench. (16th November 2020) - Masuya, Ken; Ayusawa, Ko
Abstract : The state estimation plays an essential role in controlling humanoid robots. Among the state estimation for humanoid robots, this paper targets the center of mass, the base kinematics, and the external wrench. We summarize the basic ideas to estimate them and briefly review the recent state estimators. GRAPHICAL ABSTRACT: UF0001